The Natural Termite Resistance of Teak Wood Grown in Community Forest - Ganis Lukmandaru (Jurnal Ilmu dan Teknologi Kayu Tropis, 2013)
The objective of this study was to evaluate the antitermitic activities of young teak wood through wood extracts and wood blocks samples method. Correlation between extractive content and its antitermitic properties was also studied. The disc samples from the bottom part of the five 8 years old and four 22 years old trees were sawn and samples from outer sapwood, inner sapwood, outer heartwood, and inner heartwood were prepared. Extractive contents were determined through secluded cold extraction of the wood meal using n-hexane, ethyl acetate (EtOAc) and methanol (MeOH). Force-feeding method using Reticultermes speratus Kolbe termites was used for termite resistance test. A significant interaction between tree age and radial direction factors existed with regards to the n-hexane and EtOAc extractive content. The tree age factor did not affect the mass loss levels in the extract samples. The most susceptible to termites was the sapwood of the 8 years old trees. The n-hexane and ethyl acetate extracts of the inner and outer heartwood significantly influenced the mortality rate, but in contrary to that of tree age. The EtOAc extracts of the outer heartwood was the most active antitermite. The extractive content of heartwood did not correlate to antitermite properties.Key words: antitermitic activities, community forest, extractive, Reticultermes speratus, Tectona grandis